A Matter of Dramaturgy (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
This article focuses on the development of the Khorezm Theater, the creative cooperation and stage interpretations of the actors, directors and playwrights who led the theater.